Paracetamol induced hepatic toxicity and amelioration by cinnamon in rats - Elkomy, Ashraf; Aboubakr, Mohamed; Soliman, Ahmed; Abdeen, Ahmed; Abdelkader, Afaf; Hekal, Haitham (International Journal of Pharmacology and Toxicology, 2016)
The study was designed to evaluate the hepato-protective activity of aqueous extract of cinnamon in acute experimental liver injury induced by paracetamol. Twenty four male albino rats were randomly divided into four groups (six rats in each). Group I rats received distilled water for 15 days and served as a vehicle control. The animals in the group II were given single oral administration of paracetamol (1 g/kg), 1 h after last distilled water administration and acts as paracetamol toxic control group. Groups III and IV received aqueous extract of cinnamon (200 and 400 mg/kg bwt), respectively, once daily for 15 consecutive days followed by a single oral administration of paracetamol (1 g/kg), 1 h after the last cinnamon dose administration. The degree of hepatoprotection was measured using liver enzymes (Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), bilirubin, albumin, and lipid profile levels. Also, histopathological examinations of liver were done. The significantly disturbed liver functions by paracetamol toxicity were restored to nearly normal values by administration of cinnamon. Also, the change in biochemical parameters in groups received paracetamol alone was modified towards the normal values in groups given paracetamol and cinnamon. Histopathological effect of paracetamol on liver was also markedly decreased by co-administration of cinnamon. Our findings concluded that cinnamon aqueous extracts possessed hepato-protective activity against paracetamol induced hepatic toxicity in rats.